Deconstruction of Gender and Sexuality in the I Told Sunset About You Series - Siti Shafira Nurul Hanifa; Desi Yunita; Aditya Candra Lesmana (SOCIUS, 2025)
This study analyzes the representation of gender and sexuality in the Thai series I Told Sunset About You using Jacques Derrida's deconstruction theory. Unlike previous studies that focus on identity affirmation or audience response, this research offers a new perspective by examining narrative ambiguity, emotional uncertainty, and symbolic silence as representational strategies. The research was conducted over six months (January-June 2025) by analyzing all episodes of the series, focusing on scenes that display the dismantling of masculine-feminine hierarchies, the application of différance in character relations, and the portrayal of gender identity as a fluid entity. Data were collected through dialogue transcription, scene marking, and recording of characters' gestural-emotional dynamics. The results show that this series represents queer identity not through labels, but through cues, revealing representational strategies as a form of symbolic propaganda. By emphasizing how the reproduction of space through popular media becomes a discursive space for ideological resistance, particularly related to heteronormativity. These findings contribute to the development of queer media studies in Southeast Asia, especially in reading gender politics in BL narratives critically and contextually.